2011
DOI: 10.1103/physrevb.84.220502
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field-induced stabilization of nonequilibrium superconductivity in a normal-metal/insulator/superconductor junction

Abstract: A small magnetic field is found to enhance relaxation processes in a superconductor, thus stabilizing superconductivity in nonequilibrium conditions. In a normal-metal (N)/insulator/superconductor (S) tunnel junction, applying a field of the order of 100 μT leads to significantly improved cooling of the N island by quasiparticle (QP) tunneling. These findings are attributed to faster QP relaxation within the S electrodes as a result of enhanced QP drain through regions with a locally suppressed energy gap due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 34 publications
(31 reference statements)
4
41
0
Order By: Relevance
“…Electron-phonon-mediated pair recombination has been established as the canonical mechanism of QP decay 22 . Single-QP loss mechanisms in the presence of QP 'traps', such as normal metal contacts 7,16,17,23,24 , engineered gap inhomogeneity 8,25,26 , Andreev bound states 27 or magnetic field penetration 28,29 , have also been studied.…”
mentioning
confidence: 99%
“…Electron-phonon-mediated pair recombination has been established as the canonical mechanism of QP decay 22 . Single-QP loss mechanisms in the presence of QP 'traps', such as normal metal contacts 7,16,17,23,24 , engineered gap inhomogeneity 8,25,26 , Andreev bound states 27 or magnetic field penetration 28,29 , have also been studied.…”
mentioning
confidence: 99%
“…Recently, it was also shown that a small magnetic field enhances relaxation processes in a superconductor and leads to significant improvement of the cooling power in NIS junctions. 12 Improved cooling performance can be also achieved by proper tuning of the tunneling resistances of the individual NIS tunnel junctions in a double junction SINIS cooling device. 13 Another important limitation for NIS microcoolers arises from the intrinsic multi-particle nature of current transport in NIS junctions which is governed not only by single-particle tunneling but also by two-particle processes due to the Andreev reflection.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of heat evacuation in these devices is usually solved by introducing QP traps based on normal metal inclusions [15][16][17], on the local order parameter suppression by an external magnetic field [3,[11][12][13] or by using an alternative device design immune to QP overheating [18]. The traps arising from the inverse proximity phenomenon can be effective, of course, only for the relatively low resistive devices since the noticeable gap reduction at the SN interface requires quite transparent interfaces.…”
mentioning
confidence: 99%
“…Reducing the superconducting gap the inverse proximity effect provides a physical mechanism responsible for the formation of the traps for the nonequilibrium quasiparticles (QPs) known to affect the performance of many superconducting devices such as X-ray detectors [8,9], single photon detectors [10], refrigerators based on normal metal (N) -insulator (I) -superconductor (S) junctions [11], superconducting resonators [12], superconducting qubits [13], and single-electronic hybrid turnstiles [3]. The problem of heat evacuation in these devices is usually solved by introducing QP traps based on normal metal inclusions [15][16][17], on the local order parameter suppression by an external magnetic field [3,[11][12][13] or by using an alternative device design immune to QP overheating [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation